2015
DOI: 10.2214/ajr.15.14299
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the Oropharynx With Transcervical Ultrasound

Abstract: Ultrasound is not currently used in the standard clinical evaluation of the oropharynx, but it is a promising imaging modality for evaluating the base of the tongue and the palatine tonsils. Ultrasound is comparable and complementary to CT and MRI, which have recognized limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 12 publications
1
29
0
5
Order By: Relevance
“…TCU objectively investigates the size, shape, perfusion and appearance of PT to evaluate the diagnosis and prevalence of tonsillar and peritonsillar infections [11,12]. TCU is an alternative and complementary imaging method to computed tomography and magnetic resonance imaging which have some limitations [13]. In recent times, Öztürk et al in a study of 680 cases of healthy children, including all age groups, reported that tonsil volume varied from 1.8-2.2 ml as a result of TCU measurements with a positive increasing correlation to age and BMI, though there was no difference according to gender [6].…”
Section: Discussionmentioning
confidence: 99%
“…TCU objectively investigates the size, shape, perfusion and appearance of PT to evaluate the diagnosis and prevalence of tonsillar and peritonsillar infections [11,12]. TCU is an alternative and complementary imaging method to computed tomography and magnetic resonance imaging which have some limitations [13]. In recent times, Öztürk et al in a study of 680 cases of healthy children, including all age groups, reported that tonsil volume varied from 1.8-2.2 ml as a result of TCU measurements with a positive increasing correlation to age and BMI, though there was no difference according to gender [6].…”
Section: Discussionmentioning
confidence: 99%
“…This imaging technique is particularly adapted to visualise the base of the tongue, the examination of which is challenging for anatomical reasons. Recent articles have described the sonographic appearance of the oropharynx [58] and have shown that with this technique, it is feasible to visualise and evaluate base of tongue cancers [59]. Fakhry et al [60] have assessed the benefit of ultrasonography to identify the primary site in a series of ten patients with head and neck cancers of unknown primary (HNCUPs).…”
Section: Identification Of Lesions In Individuals With a Positive Scrmentioning
confidence: 99%
“…The use of imaging techniques such as computed tomography (CT) and magnetic resonance imaging (MRI) have been reported to be useful for the evaluation of peritonsillar abscesses and the overall volume of the tonsils; however, these techniques have a number of limitations, such as a requirement of sedation, exposure to radiation, and/or a high cost. Recently, the use of ultrasound for evaluating the tonsils has been reported, which represents a less expensive, more portable, and more rapidly available technique with better tissue resolution. Furthermore, because ultrasound does not require sedation, and eliminates the need for ionizing radiation, it could be particularly advantageous for examining children.…”
mentioning
confidence: 99%
“…To our knowledge, all previous reports in which ultrasound was used to examine the tonsils have been limited to case reports, pictorial essays, or technical notes …”
mentioning
confidence: 99%
See 1 more Smart Citation